The Commonwealth of Independent States - Resnick, Abraham; Nang ChanYeema (United States of America Childrens Press, 1993)
Describes how the Commonwealth of Independent States came about after the collapse of the Soviet Union and introduces the geography, people, and culture of the Commonwealth's republics.
Keywords: Adult Nonfiction